2012
DOI: 10.1186/1550-2783-9-s1-p5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 weeks of beta-hydroxy-beta-methylbutyrate free acid gel supplementation on muscle mass, strength, and power in resistance trained individuals

Abstract: Previous research in trained individuals supplemented with beta-hydroxy-beta-methylbutyrate (HMB) has been constrained to short (<10 weeks), non-periodized studies, lacking dietary control, that were subject to poor outcome measures (e.g. skin caliper measurements). These conditions make it difficult to determine HMB's effects in athletes. The primary purpose of this study was to investigate the effects of 12 weeks of HMB free acid (HMB-FA) supplementation in trained individuals on direct skeletal muscle hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The first consideration involves the dosage of HMB. Whereas most prior studies involving HMB used a 3-g/day split over three doses during the day (10,33,35,56), a recent study (57) found that a bolus of HMB (3.42 g) was also successful in reducing muscle-protein breakdown, while promoting muscle-protein synthesis. In addition, Wilson et al (58) found a 3-g bolus of HMB-Ca to significantly attenuate indices of muscle damage when taken before exercise (58).…”
Section: Discussionmentioning
confidence: 99%
“…The first consideration involves the dosage of HMB. Whereas most prior studies involving HMB used a 3-g/day split over three doses during the day (10,33,35,56), a recent study (57) found that a bolus of HMB (3.42 g) was also successful in reducing muscle-protein breakdown, while promoting muscle-protein synthesis. In addition, Wilson et al (58) found a 3-g bolus of HMB-Ca to significantly attenuate indices of muscle damage when taken before exercise (58).…”
Section: Discussionmentioning
confidence: 99%
“…Dunsmore and colleagues [ 187 ] assessed the effects of 3 g/day HMB free acid (FA) or a placebo over the course of a 12-week periodized resistance training study. Following the 12-week intervention, strength, power, and muscle hypertrophy improved among the HMB supplement group.…”
Section: β-Hydroxy-β-methylbutyratementioning
confidence: 99%
“…Normal plasma range of HMB concentrations is 1 to 4 µmol/L, but can increase 5-to 10-fold following leucine administration [32]. Although some foods including citrus fruits, some fish, and breast milk have a mount of HMB [29], it is impractical to provide the typical 3 g daily dosage of HMB used in most previous human studies that demonstrate improvement of body composition [5,6,[8][9][10], and muscle strength [5,[8][9][10][11][12]. Therefore, HMB supplementation is a reasonable way for different athletes, specifically, those who participate in resistance training programs to obviate the recommended daily amount of HMB.…”
Section: A Brief Overview Of Hmb Metabolismmentioning
confidence: 99%
“…Scientific researches during the past 20 years demonstrate that HMB supplementation in conjunction with resistance training may improve body composition [5][6][7][8][9][10], muscle strength [5,[7][8][9][10][11][12] and power [5,8,11]. It has also been reported that supplying HMB promotes favorable changes in aerobic [13][14][15] and anaerobic [9,13,16] capacity, and muscle recovery after exercise [10,[17][18][19][20] in different athletes. To date, several systematic reviews and meta-analyses have investigated the aforementioned actions of HMB supplementation in a variety of populations [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%